Artificial Intelligence Introduction Assistance for Children in Karangsari Village, Sapuran District, Wonosobo Regency - Halim Purnomo; Hisyam Syafii (CV. Doki Course and Training, 2025)
This program aims to improve children's digital literacy in Karangsari Village, Sapuran District, Wonosobo Regency, through basic introduction to Artificial Intelligence (AI) to bridge the digital divide between urban and rural areas which was carried out on January 28-29, 2025. The methods used include the preparation, implementation, and evaluation stages, with a participatory approach that includes socialization, interactive training, and direct assistance. Evaluation is carried out through observation, interviews, questionnaires, and simple tests to measure participants' understanding and skills. The results show a significant increase in understanding basic AI concepts and the ability to apply AI-based technology, as well as strengthening soft skills such as cooperation and critical thinking. However, there are several obstacles faced, such as limited technological devices, unstable internet access, and differences in participants' levels of understanding, so further strategies are needed in providing supporting infrastructure and more inclusive and adaptive learning methods.